Stress-induced nanoscale phase transition in superelastic NiTi by in situ X-ray diffraction. (15th May 2015) - Ahadi, Aslan; Sun, Qingping
Abstract: In situ X-ray diffraction during loading and unloading is used to investigate the effects of grain size (GS) on the stress-induced nanoscale phase transition (PT) mechanism in polycrystalline superelastic NiTi. The average GS studied (10–1500 nm) spans the range in which significant changes of macroscopic thermomechanical properties (due to GS reduction) have been observed. It is shown that when the GS ⩾ 68 nm, the evolution of the diffraction profiles (DPs) during loading and unloading exhibits well-defined distinct diffraction peaks with significant changes in their diffracted intensities corresponding to the nucleation and growth mechanism of B19′ martensite (high strain) phase. However, when GS < 68 nm, the evolution of DPs gradually degenerates from the multiple peaks mode to a continuous and reversible single peak shift mode. Measurements of the lattice parameters and the corresponding components of lattice strains show that such drastic changes in characteristics of DPs indicate a gradual change in the PT mechanism from traditional nucleation and growth mode in coarse-grained polycrystals to a continuous lattice deformation inside the nano-sized grains. Moreover, the middle eigenvalue ( λ 2 ) of the transformation matrix gradually approaches 1 with GS reduction, almost fulfilling the proposed λ 2  = 1 condition in the literature for the vanishing of hysteresis in SMAs. The results provide lattice level scenarios for the understanding of GS effects on the change of PT type from first-order to continuous PT which brings significant changes in the macroscopic thermomechanical behavior and properties of the polycrystalline superelastic NiTi.